CONTROLLING CORRUPTION TO STRENGTHEN THE ROLE OF THE EDUCATION BUDGET FUNCTION IN ACHIEVING SDG 4 IN INDONESIA - Ramadani, Nadila Wulan; Furqan, Andi Chairil; Rahma Masdar; Fajar Gilang Yudistira (Journal of Applied Finance and Accounting, 2025)
Disparities in education budgets across regions, limited access to remote areas, and low participation rates at all educational levels represent significant challenges for Indonesia in achieving SDG 4 by 2030. This study investigates the contribution of education function expenditure to attaining SDG 4, with corruption control as a moderating variable. Utilizing 1,016 observations of secondary data from provincial, district, and city governments during 2021–2022, the findings reveal that education budgets substantially support SDG 4 achievement. However, overly procedural corruption control mechanisms diminish the effectiveness of budget utilization by restricting the flexibility in fund allocation. The scientific contribution of this research lies in providing empirical evidence on the moderating effect of corruption control on the effectiveness of education budgets in achieving SDG 4. From a practical standpoint, the study recommends the adoption of adaptive, risk-based corruption control mechanisms such as Risk-Based Internal Audit and performance-based fund disbursement systems to strike a balance between accountability and flexibility in budget management. This study is limited to district and city-level data over  two years and focuses exclusively on the education function, thus, its findings may not fully represent conditions at the provincial level or other SDG sectors. Future research should broaden data coverage and incorporate qualitative methodologies to deepen understanding of bureaucratic processes and corruption control dynamics.